Optimizing the Performance of Education Personnel: A Review of Performance Allowance and Motivation Factors at Maranatha Christian University - Fajarsyah, Bintang; Anatan, Lina (Syntax Literate, 2024)
This study aims to examine how performance allowances and motivation affect Maranatha Christian University education staff's performance. The study population consisted of all 292 educational staff at Maranatha Christian University. The sample size was established using the Slovin method, yielding a sample of 75 respondents. Using Full Model Regression, a multiple linear regression equation was obtained: Y = 12.051 + -001 X1 + 0.072 X2. From this equation, it can be deduced that the coefficient of determination (r2) is 0.466, meaning that the X1-X2 variables may account for 46.6% of the model's variance while the remaining variance (53.4%), which is not accounted for by this regression model, is explained by other variables. The calculated F value was 33,249, with a significant F of 0.000 < 5%. This supports the hypothesis that Ho: b1= b2 â‰  0, meaning that both factors (X) have an impact on Y.